Ukuran dan Hubungan Panjang Berat Dua Spesies Ikan Senangin Hasil Tangkapan Nelayan Jaring Insang sebagai Bahan Ajar Ekologi Hewan - Ghaitsa Zahira Shofa; Khairul Khairul; Hasmi Syahputra Harahap (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to examine the growth aspects of the fourfinger threadfin (Eleutheronema tetradactylum) caught in the waters of the Barumun River, Labuhanbatu Regency, North Sumatra. The research was conducted using a survey method, with fish samples collected from traditional fishermen in Telaga Suka Village using gill nets. The total length of the fish was measured using a ruler with an accuracy of 0.01 mm, and the weight was measured using a digital scale with an accuracy of 0.05 mg. Data analysis included size distribution based on Sturges’ rule and the length-weight relationship using a logarithmic approach. The results showed that the river-caught E. tetradactylum had a relatively even size class distribution ranging from 195–315 cm, while the bubble threadfin exhibited more varied sizes ranging from 138–168 cm. The length-weight relationship for both species indicated a negative allometric growth pattern, with b values of -3.9984 (river threadfin) and -5.5749 (bubble threadfin), indicating that length growth occurs faster than weight gain. In conclusion, E. tetradactylum in the Barumun River shows growth influenced by environmental factors, fishing gear, and anthropogenic activities. The species holds significant economic value for local communities, and thus its management should be directed toward sustainability. Keywords: Allometric, Barumun River, Freshwater Ecosystem, Growth, Threadfin Fish